Cotransfer of thymidine kinase and galactokinase genes by chromosome-mediated gene transfer. - McBride, O W (1978)
The Chinese hamster genes for thymidine kinase (ATP:thymidine 5'-phosphotransferase, EC 2.7.1.75) and galactokinase (ATP:D-galactose 1-phosphotransferase, EC 2.7.1.6) have been cotransferred to mouse cells by chromosome-mediated gene transfer. Hamster metaphase chromosomes were incubated with mouse B82 cells and 22 independent colonies were isolated in a selective medium. All of the 12 colonies analyzed expressed the donor form of thymidine kinase; the hamster form of galactokinase was also expressed in 2 of these colonies, indicating cotransfer with a frequency of about 20%. There was coordinate loss of both transferred genes from each colony when selection was applied for the loss of thymidine kinase alone. Comparison of the regional localization of these two linked genes with the frequency of cotransfer suggests that the transgenome is probably not larger than about 0.25% of the donor genome.